Ethnobotanical survey of indigenous leafy vegetables in Ehlanzeni District of the Mpumalanga Province, South Africa - Madonna N. Mashabela; Wilfed Otang Mbeng (AOSIS, 2021)
Background: There is a high loss of indigenous knowledge, resulting in negative effects on the health and lives of cultural people living in poor communities mostly in the rural areas, hence, an urgent need for indigenous knowledge conservation. Aim: This study is aimed at presenting the potentials of leafy indigenous vegetables as an essential source of food and nutrition for poor communities. We argue that through knowledge transfer, these species have a chance of being revitalised and used, thereby conserving plant biodiversity while ensuring food and nutrition security. Setting: An ethnobotanical survey was conducted in the Ehlanzeni District of the Mpumalanga Province, South Africa, to uncover and document the indigenous leafy vegetables (ILVs) from the area as well as to evaluate the community's indigenous vegetable knowledge and utilisation state. Methods: Using a structured questionnaire, 95 respondents were interviewed. Older women were particularly targeted since they are the repositories of ethnobotanical information related to ILVs. Results: The study revealed 17 indigenous leafy vegetable species from 10 families. About 85% of the ILVs cited possessed medicinal properties. The most common means of preservation was sun-drying, although consumption of vegetables in their fresh state was most preferred. Conclusion: High blood pressure was cited to be treated by most of the ILVs; therefore, there is a need to include these vegetables in our daily diets.